Analisis Pengaruh Retak Terhadap Ketangguhan Baja Karbon Rendah Dengan Parameter Integral J - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Biologi UGM, 2000)
The material toughness test using a J-integral parameter has been carried out using two methods, namely direct method and unloading method. Calculation of Jic was performed based on yield point, first load drop, initial crack growth and fracture criteria. The J-integral parameter obtained from experimental results was then compared with stress intensity factor (K) for the same material. The stress intensity factor test was carried out in accordance with the ASTM E-399 procedures. The type of specimen for both J-integral and stress intensity factor was compact tension specimen (CTS) with three different thickness, namely 13,5 mm, 20,0 mm and 23,0 mm. The measurement results give the average value of stress intensity factor, Kc = 147,01 kg/min", 185,67 kg/inin'f2 and 207,38 kg/mre2 for the thickness of 13,5 mm, 20,0 mm and 23,0 mm, respectively, In addition, the average value of .1- integral parameter is 11,32 kg/mm. The value of .1-integral for the specimen with different thickness is relatively the same. Therefore, this parameter provides an alternative solution to determine the toughness of low carbon steel